Assessing the Implementation of Renewable Energy Policy within the UAE by Adopting the Australian 'Solar Town' Program. Issue 1 (15th November 2019) - Shareef, Sundus; Altan, Hasim
The environmental policies and the use of renewable energy are at the highest priority of the United Arab Emirates' (UAE) plans and strategies, and the implementation of clean energy in the country is one of the recent environmental practices that would require more studies and investigation. Conducting this study will offer some valuable analyses and results that could be taking into consideration in the implementation of renewable and solar energy programs further to enacting the environmental legislations and policies to achieve the UAE's target of reducing CO2 emissions 70% by 2050. This study aims to explore the capability of implementing the solar panel (PV) system on a large scale by adopting the 'Solar Town' program and policies developed by some of the leading countries such as Germany and Australia. Further to this, Cost Benefit Analysis (CBA) was conducted to explore the benefit and the payback period of implementing this program. By calculating the CBA for each property within the community, it has been found that the PV energy system could cover an apartment's electricity consumption with a 1.1 kW surplus, while it can cover only 60% of a villa's electricity consumption.